Local cases in educational management - Abad, Corazon S. 1937-
Case No.1, "Pressure to Render Accounting of Public Trust Funds and to Rid of Bogus Athletes" deals with the problems faced by a division superintendent of schools in soliciting public cooperation and support for a regional athletes meet when public demand strongly called for an accounting of the funds disbursed in a previous athletic meet and a promise to stop hiring bogus athletes. Case No.2, "Democratization of University of the Philippines Admission Policies," traces the origin and development of a recent major policy in the state university and describes the proposed strategies being developed to insure its effective implementation. Case No.3, "Campus Press Freedom and Responsibility" involves a question of policy with respect to the regulation and control of student publications in a state college. Case No.4, "The University of the Philippines Integrated School", describes the plan and strategies for eliciting and ensuring faculty participation in the integration of the elementary and high schools of the University of the Philippines into a single unit.